Wages : a Means of Testing Their Adequacy - Leeds, Morris Evans (University of Pennsylvania Press, 2017)
This book is a volume in the Penn Press Anniversary Collection. To mark its 125th anniversary in 2015, the University of Pennsylvania Press rereleased more than 1,100 titles from Penn Press's distinguished backlist from 1899-1999 that had fallen out of print. Spanning an entire century, the Anniversary Collection offers peer-reviewed scholarship in a wide range of subject areas.
Keywords: Wages -- United States.; Cost and standard of living -- United States.; Working class -- United States.; Home economics -- Accounting.; Coût et niveau de la vie -- États-Unis.; Travailleurs -- États-Unis.; Budgets familiaux.; BUSINESS & ECONOMICS -- Econometrics.; Cost and standard of living; Home economics -- Accounting; Wages; Working class; United States; Business.; Economics.